Histological Evaluation of Effect of beta-Tricalcium Phosphate on Bone healing in Alloxan-Induced diabetes - Noor Abdulkareem Razouki; Ban A. Ghani (College of Dentistry/ University of Baghdad, 2016)
Background: Improved glucose level control with insulin injections have allowed for the diabetic population to live longer and healthier lives. Unfortunately diabetes remains a worldwide epidemic disease with multiple health implications. Specifically, its effects upon fracture healing are compromised in diabetics with as high as 87% recovery delay relative to "healthy" counterparts. Current medical treatments for bone injuries have been largely focused on replacing the lost bone with allogenic or autogenous bone grafts, beta-tricalcium phosphate (β -TCP), a ceramic alloplast, has interconnected system of micropores, has been widely used as a biologically safe osteoconductive bone substitute. The aim of this study was histological evaluation of effect of topical application of β -TCP on bone healing of diabetic rabbit. Materials and methods: Sixty New Zealand rabbits used in this study were divided into three groups for four healing intervals the experimental groups were: 1-Control group(C).2-Diabetic rabbits received insulin treatment regarded as controlled diabetes mellitus (CDM)group.3-Diabetic rabbits did not receive any treatment regarded as uncontrolled diabetes mellitus (UDM)group. All animals subjected to surgical operation in right tibia, creating bone defect 3mm in depth and 4mm in diameter filled with β-Tricalcium Phosphate. Animals' scarifications were done in 5 day, 2, 4 and 6 weeks durations. Routine processing and sectioning technique was performed for histological evaluation. Results: Histological findings indicated that bone defects in control(C) and controlled diabetes mellitus (CDM) groups showed early bone formation, mineralization and maturation in comparison to healing of uncontrolled diabetes mellitus (UDM) group. Histomorphometric analysis for all bone parameters examined in this study, showed variation in significance among all groups in different durations. Conclusion: The study revealed that application of β-TCP was more effective in enhancement of bone regeneration and in acceleration of bone healing process in controlled diabetes as compared to the uncontrolled one.